MANAGING THE STUDENTS’ INTERACTION IN TEACHING READING THROUGH TASK-BASED LEARNING - Yelfiza, Yelfiza (English Department FBS UNP, 2010)
This paper discusses managing the senior high school students’ interaction through task-based learning. The writer has collected some theories from some experts about interaction and task based learning. It is true that interaction in learning will be managed by the teacher, in this case, through task-based learning. Having analyzed and discussed the theories, the writer can draw conclusion that English competencies could be gained if the teacher can provide English environment for the students. The more the teacher can provide English environment in learning process, the better English competencies the students can master. Therefore, the teacher is suggested to expose English very frequently, so that the students can listen, speak, read, and write English. These activities can be done by involving the students in interaction through task-based learning by building control of the field task, modeling, having joint construction, and having independent construction.